Diffusion MRI : from quantitative measurement to in-vivo neuroanatomy - Johansen-Berg, Heidi; Behrens, Timothy E. J. (Amsterdam ; Boston : Elsevier/Academic Press, 2009)
Includes bibliographical references and index.